The enhancement of critical thinking using halaqah method among students of Dayah in Dayah Mudi Mesjid Raya Salamanga, Aceh - Al Munadia (Kulliyyah of Education, International Islamic University Malaysia, 2016)
This study investigated the enhancement of critical thinking skills using halaqah method among dayah students at Dayah Mudi Mesjid Raya Samalanga Aceh, Indonesia. It examined the teachers' perceptions and practices of critical thinking in the classroom. The major theory of this study is based on Bloom's Taxonomy types of questions and levels of thinking. Participants in the study were selected using purposive sampling.The researcher employed qualitative design with semi-structured interviews, focus group discussion and classroom observations as methods of data collection. The respondents consisted of three teachers and five students from grade 5-D. The data from interviews, and focus group discussion were analyzed using thematic analysis, while the observations were analyzed using content analysis against Bloom's Taxonomy levels of thinking. The findings showed that the teachers perceived that they are teaching critical thinking to their students. The evidence of critical thinking among students was perceived in their ability to ask questions, evaluate opinions, understand the information presented, to respond and communicate it to others. However, teachers did not seem to understand the requirement needed to cultivate critical thinking among students and they were merely focusing on the comprehension of the subject matter. The results also showed that LOT questions were much higher posed by the teacher and students than HOT questions. Some of the recommendations for future studies include a larger sample in both traditional and modern Islamic schools at different levels.